Management of recurrent epithelial ingrowth following laser in situ keratomileusis with mechanical debridement, alcohol, mitomycin‐C, and fibrin glue. Issue 7 (July 2017) - Wilde, Craig; Messina, Marco; Dua, Harminder S.
Abstract : N/A: We report a consecutive case series of 4 eyes in which recalcitrant epithelial ingrowth after laser in situ keratomileusis was treated with flap lift, mechanical debridement of epithelial ingrowth, sequential application of alcohol 70.0% and mitomycin‐C (MMC) 0.02% to residual epithelium and across the stromal bed and underside of the flap. Secure flap apposition was achieved with the use of fibrin glue. Clinically significant epithelial ingrowth did not recur in any eye; visual acuity improved in all cases. No complications were associated with this treatment. Mechanical debridement of epithelial ingrowth with additional application of alcohol 70.0% and MMC 0.02% along with tissue glue use for flap closure appears to be a safe and effective treatment for recalcitrant cases of clinically significant epithelial ingrowth.